2018
DOI: 10.1159/000493574
|View full text |Cite
|
Sign up to set email alerts
|

Within-Population Variations in Home Range Use and Food Patch Use of Japanese Macaques: A Perspective of Intergroup Hostility

Abstract: Behavioral mechanisms of intergroup feeding competition remain unclear, despite its importance as a benefit of group living. Japanese macaques in the coastal and highland forests of Yakushima, Japan, are ideal study subjects because the intensity of intergroup feeding competition differs without phylogenetic effects. We aimed to test whether macaques modify home range use and food patch use in response to the location-specific risk of intergroup encounters. Using behavioral data from 3 groups, we examined the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…Large‐scale hydrothermal conditions (incorporating temperature and precipitation) are essential for determining species distribution. Limiting factors include deforestation, hunting, group size, sex ratio, competition, food habits, and resource availability which are directly related to species distribution (Jiang et al, 2020; Kurihara & Hanya, 2015, 2018). In recent years, many previously destroyed forests have been restored, and the decline in hunting has had a positive effect on the populations of many endangered species and increased their distribution (Luo et al, 2015; Ruan & Huang, 2014; X. Zhao et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Large‐scale hydrothermal conditions (incorporating temperature and precipitation) are essential for determining species distribution. Limiting factors include deforestation, hunting, group size, sex ratio, competition, food habits, and resource availability which are directly related to species distribution (Jiang et al, 2020; Kurihara & Hanya, 2015, 2018). In recent years, many previously destroyed forests have been restored, and the decline in hunting has had a positive effect on the populations of many endangered species and increased their distribution (Luo et al, 2015; Ruan & Huang, 2014; X. Zhao et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…For example, while many species occupy home ranges with undefended boundaries, others maintain actively defended territories (Powell, 2000). In species with intense and potentially lethal intergroup competition, individuals tend to avoid areas near territorial boundaries, where they are likely to encounter neighbouring individuals (Mech & Harper, 2002;Sillero-Zubiri & Macdonald, 1998;Wrangham, Wilson & Hauser, 2007), and are more alert when moving through these locations (Kurihara & Hanya, 2018;Tórrez-Herrera et al, 2020;Wrangham, Wilson, et al, 2007). Indeed, Moorcroft et al (1999) showed how individual coyotes' (Canis latrans) avoidance of areas with a high probability of encountering the scent marks of individuals from neighbouring pair of individuals with a hard territorial border between their home ranges; and…”
Section: Introductionmentioning
confidence: 99%
“…For example, while many species occupy home ranges with undefended boundaries, others maintain actively defended territories (Powell, 2000). In species with intense and potentially lethal inter-group competition, individuals tend to avoid areas near territorial boundaries, where they are likely to encounter neighbouring individuals (Sillero-Zubiri & Macdonald, 1998;Mech & Harper, 2002;Wrangham et al, 2007a,b), and are more alert when moving through these locations (Wrangham et al, 2007b;Kurihara & Hanya, 2018;Tórrez-Herrera et al, 2020).…”
Section: Introductionmentioning
confidence: 99%